Unraveling pathologies underlying chromosomal instability in cancers. Issue 8 (11th June 2021) - Jo, Minji; Kusano, Yoshiharu; Hirota, Toru
Abstract: Aneuploidy is a widespread feature of malignant tumors that arises through persistent chromosome mis‐segregation in mitosis associated with a pathological condition called chromosomal instability, or CIN. Since CIN is known to have a causal relationship with poor prognosis accompanying by multi‐drug resistance, tumor relapse, and metastasis, many research groups have endeavored to understand the mechanisms underlying CIN. In this review, we overview possible etiologies of CIN. The key processes to achieve faithful chromosome segregation include the regulation of sister chromatid cohesion, kinetochore‐microtubule attachment, bipolar spindle formation, spindle‐assembly checkpoint, and the activity of separase. Aberrant chromosome structures during DNA replication might also be a potential cause of CIN. Defective regulation in these processes can lead to chromosome mis‐segregation, manifested by lagging chromosomes, and DNA bridges in anaphase, leading to gross chromosome rearrangements. Investigation into the molecular etiologies of CIN should allow us to explore novel strategies to intervene in CIN to control cancers. Abstract : There are two major pathways in mitosis that lead cells to chromosome mis‐segregation. Defective correction of erroneous microtubule attachments causes lagging chromosomes and defective SAC inactivation and subsequent separase activation causes chromosomal bridges.